TINJAUAN YURIDIS TERHADAP PELANGGARANPEMASANGAN PAPAN NAMA NOTARIS ( STUDI DI KABUPATEN SLEMAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - NINGRUM, ANITA NOVIANA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The research entitled “Juridical Analysis of the Offense of Notary Sign Installation (Study in the District of Sleman, Yogyakarta)” aims at examining the action of sign installation by Notary in the District of Sleman, examining the forms of offense of sign installation by Notary as well as an offense toward Notary Ethic, and examining the process of supervising those who commit the offense of sign installation. This is an empirical juridical research applies secondary and primary data by way of literature research and fieldwork. The subjects of research are respondent and resource person know of the research questions. The sample was collected using a technique of non probability sampling in which the sample was taken by way of Purposive Sampling that is determining the prospective respondent based on certain criteria. The data was analyzed by applying qualitative approach and presented descriptively. The finding shows that in the District of Sleman there are Notaries whose sign installation does not comply with the regulation of Notary Ethic. The form of offense mostly committed is the installation of road sign. This offense occurs due to Notary supervising in the District of Sleman that is not optimum yet which causes a number of Notaries commit the offense of sign installation.